Workflow for building and calibrating 3D pre-injection and 4D geomechanics modelling to assess caprock and fault integrity for geologic CO2 storage - Aminu, Mohammed Dahiru; Ardo, Buhari U.; Jato, Musa A. (Slovnaft VÚRUP, 2017)
Carbon capture and storage (CCS) has been established as a viable technology for the mitigation of climate change caused mainly by anthropogenic greenhouse gas emissions into the atmosphere. Ever since the publication of the special report on CCS by the Intergovernmental Panel on Climate Change in 2005, there has been an increased research and development in all areas of CCS. Some of these research involves use of numerical methods and models for optimizing storage and ensuring effective long term containment. In this paper, we propose a workflow for building and calibrating 3D preinjection and 4D geomechanics modelling to assess caprock and fault integrity for geologic carbon dioxide storage. The workflow presented here describes a seamless end -to-end process which combines a transparent flow of data with an easy-to-use graphical user interface. The workflow can conduct 3D static and 4D flow-, pressure-, and temperature-coupled calculations for rock deformations, failure and stresses. In highly heterogeneous and complex models, the workflow is capable of modelling multiple hundred faults, and multiple thousand discrete fractures. It allows the geological model, despite its high degree of complexity to be maintained throughout the geomechanical analyses process.
Keywords: Workflow; Caprock; Fault; CO2 storage; Bunter sandstone formation